نموذج تعلّم اللغة العربية في عصر العولمة من خلال نهج تواصلي رقمي: MODEL OF ARABIC LANGUAGE LEARNING IN THE ERA OF GLOBALIZATION THROUGH A DIGITAL COMMUNICATIVE APPROACH - Budiriyanto, Anis (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2024)
In the era of globalization, Arabic language learning faces unique challenges in adapting to the global flow, specifically by utilizing information technology as the primary source and medium. The purpose of this study is to explore the model of Arabic language learning through a digital communicative approach. The method used in this research is library research. The findings indicate that in the globalization era, the model of Arabic language learning through a digital communicative approach involves learning strategies such as discussions, Q&A sessions, problem-solving, report writing, message exchanges, and online writing. Keywords: Arabic language learning, Era of Globalization, Digital communicative approach.